Robotics - The answer to the Achilles' heel of VATS pulmonary resection - Dylewski, Mark R.; Lazzaro, Richard S. (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
During the past decade, robotic surgical systems have been increasingly utilized to perform highly complex surgical procedures. In fact, the robotic-assisted approach to the treatment of many gynecological and urological surgical procedures has become the standard-of-care. The use of robotic surgical system in thoracic surgery is in its early development. Video-assisted thoracoscopic surgery (VATS) was propelled forward in the early 1990’s without full appreciation for long-term consequences, increased cost or therapeutic benefit. The trend in robotic-assisted thoracic surgery is projected to surpass the adoption of VATS and to mirror that of other robotic surgical subspecialties.